1990
DOI: 10.1111/j.1751-1097.1990.tb01726.x
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine Fluorescence in Tumors During PDT

Abstract: Athymic nude mice with human tumors transplanted to one of the hind legs were given aluminium phthalocyanine disulfonate (AlPcS2) intraperitoneally. Twenty-four hours after the injection the mice were placed with the tumor in the sample position in a fluorescence spectrometer with modulated excitation. Exposure of the tumors to laser light at a fluence rate of 50-200 mW/cm2 led to a rapid transient reduction by up to 50% of the phthalocyanine fluorescence of the tumor. After the laser irradiation the fluence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…Over the past decade, they have also attracted attention as functional chromophores for applications as organic charge carriers in photocopiers [2], as laser light absorbers in data storage systems [3,4], as photoconductors in photovoltaic cells [5], and in electrochromic displays [6]. Moreover, particular derivatives are known to have potential as second-generation photosensitisers for photodynamic therapy (PDT) of cancer [7] because they show strong absorption of far-red light between 600 and 850 nm wavelength which has a greater penetration of tissue [8], and satisfactory photosensitisation of singlet oxygen [9].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, they have also attracted attention as functional chromophores for applications as organic charge carriers in photocopiers [2], as laser light absorbers in data storage systems [3,4], as photoconductors in photovoltaic cells [5], and in electrochromic displays [6]. Moreover, particular derivatives are known to have potential as second-generation photosensitisers for photodynamic therapy (PDT) of cancer [7] because they show strong absorption of far-red light between 600 and 850 nm wavelength which has a greater penetration of tissue [8], and satisfactory photosensitisation of singlet oxygen [9].…”
Section: Introductionmentioning
confidence: 99%
“…All animals were treated with a total light dose of 50 J. The effect of varying the light delivery regimen was studied using a drug-light interval of 24 h as our previous work and that of others using AlSPc in normal liver (Bown et al, 1986), and small rodent tumours (Tralau et al, 1987;Moan and Anholt, 1990) had shown a more homogeneous drug fluorescence distribution at this DLI compared with shorter times. Drug light intervals of 1 and 3 h were studied with a fixed light delivery regimen of 100 mW, continuous.…”
Section: Oxygen Saturation Measurementsmentioning
confidence: 99%
“…This is inferred from the observation that only in this case did D 2 0 enhance the rate of fluorescence change (Figure 1) . Moan and Anholt (1990) have recently observed fast transient changes in A1PcS 2 fluorescence in tumours during PDT. Our measurements were made about 2 min after illumintion, a time at which these transient changes disappear, and thus are unlikely to contribute to the changes in A1Pc fluorescence reported in this paper.…”
Section: Discussionmentioning
confidence: 98%